Itinerários de um serviço de saúde mental na cidade de São Paulo: trajetórias de uma saúde poética - Galletti, Maria Cecília (2007)
The propose of this doctorate dissertation is to map the ways to a mental health service in São Paulo County Centro de Convivência e Cooperativa Parque Previdência , and most specially to raise questions about the management issues that we are experiencing. This management attitude that rearranges the clinical subjectivity system was adopted in this research as a method that moves away from the perspective of analysis of extensive approaches to a process that constituted itself as a political clinical device capable of transversalizing the public domain of health policies in its relation with the State. Intensivist method. This text received the support of authors engaged mainly with the Philosophy of Difference, and goes along with the method in the deconstruction of a traditional model of health care, which identifies the management with the position of a person (as a manager) to give life to a management function that is no longer an individual practice, but rather reaches its fulfillment in the network connective experiment. We call poetic health this experience of network management, which is improving health in new ways of life care, and is promoting the inclusive work processes, since it deals with collective communities and subjectivities